Masters in Clinical Laboratory Science at University of Texas Medical Branch, a Success Story...American Society for Clinical Laboratory Science (ASCLS) Clinical Laboratory Educators’ Conference (CLEC), February 25-27, 2016 in Minneapolis, Minnesota. - Jianzhi Zhang; Esani, Muneeza (Clinical Laboratory Science)
The goal of Clinical Laboratory Science (CLS) Master's program is to provide quality laboratory practitioners with skills in applying Evidence-based Laboratory Science and leadership to benefit the patients and profession that they serve and to contribute to the scientific knowledge in CLS. The University of Texas Medical Branch introduced three new Master's degree programs in CLS in 2011. This program consists of three tracks which include a Masters in science for students with no CLS background, a distance Master's in science for individuals who already hold a bachelor's degree in CLS and a distance Master's in Science in Transfusion Medicine. The program started with 5 students in 2011 and we currently have 35 Masters Students between the three tracks. This program will have graduated 23 students by the end of year 2015. Students complete graduate level clinical laboratory science courses while in the program. The culminating experience of the master program in clinical laboratory science is the completion of a thesis. The intent and construct of a thesis varies by research project area and its supervision is handled by a member of CLS Faculty as a thesis chair, a course instructor and the Master's thesis committee consisting of CLS faculty members. Distance students are allowed to also have a research mentor at their clinical facility. Graduate satisfaction and professional advancement indicate that CLS Master's program is a success story. This poster will focus on the design and implementation of a CLS Master program and will also include graduate success stories.